Dança e decolonialidade no palco da escola: experiência pedagógica no ensino fundamental II. - SILVA, Thaís de Brito (2020)
The dance as an artistic language is a mandatory content in the elementary school. An achievement that occurred in the 80´s by the struggle for art in the education, historically marked by the Eurocentric epistemological hegemony in the schools. This reinforces the prejudices, the denial of the arts from the ethnical minority groups and contributing for an ethnocentric behavior in the school community. In a reality observed in the Severiano de Azevedo City School – Anexo Sertãozinho, one may verify that students and staff are distant to the speech about arts and the rejection by the afros-amerindian culture. A challenge of teaching dance in the elementary school II is noted as a reflex of a colonialist education, which the knowledge installed in the afros-indigenous matrix culture were silenced in Brazil by the European hegemonic arts, as a form of catechization, politics and domination of a class. In the present study, the objective was to develop a pedagogical experience with the students from the elementary school II which enables a decolonial education using investigations about dances that originates from afros-indigenous rituals. With regards to the methodology, as it aims to develop a solution to a problem and involves a local interest, this research is of a theorical-pratical applied nature, with a quanti-qualitative problem approach and an exploratory character. In order to evaluate the dance/school relationship, the technical instruments adopted was bibliographic survey, study cases, research-action, interview with the school principal and students. And, due to the study focused on a theme that present few academic references, a descriptive approach was also set up, once it was intended to exhibit the ethnical and ritualistic dances characteristics from Maranhão, specifically from Icatu. In this work, dialogs of sociological, anthropological, educational and artistic nature were articulated using theoretical references from Stuart Halls, Néstor Canclini, Homi Bhabha, Aníbal Quijano and the Argentinian semiologist Mignolo. The themes correlated to the dances and rituals were based on the approaches of Roger Garaudy, Lícia Shancez, Isabel